2010
DOI: 10.1016/j.jacc.2009.08.074
|View full text |Cite
|
Sign up to set email alerts
|

Increased Oxidative Stress and Cardiomyocyte Myofibrillar Degeneration in Patients With Chronic Isolated Mitral Regurgitation and Ejection Fraction >60%

Abstract: Objectives We assessed myocardial damage in patients with chronic isolated mitral regurgitation (MR) and LV ejection fraction (EF) > 60%. Background MR patients typically have decreased LVEF after mitral valve (MV) repair despite normal pre-operative LVEF. Methods 27 patients with isolated MR had LV biopsies taken at time of MV repair. Magnetic resonance imaging with tissue tagging was performed in 40 normal subjects and in MR patients pre- and 6 months post-MV repair. Results LVEF (66 ± 1 to 54 ± 2% p<0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
125
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(136 citation statements)
references
References 32 publications
10
125
1
Order By: Relevance
“…These changes at short-term reversal were associated with increased cEDS, which is consistent with reported increased cEDS and reduced systolic function following mitral repair in canine hearts (36), adults (3,26), and children with congenital MR (22). The underlying mechanisms responsible for decreased systolic performance are unclear and may be attributed to changes in gene and protein expression, force generation, or Table 3.…”
Section: Discussionsupporting
confidence: 81%
“…These changes at short-term reversal were associated with increased cEDS, which is consistent with reported increased cEDS and reduced systolic function following mitral repair in canine hearts (36), adults (3,26), and children with congenital MR (22). The underlying mechanisms responsible for decreased systolic performance are unclear and may be attributed to changes in gene and protein expression, force generation, or Table 3.…”
Section: Discussionsupporting
confidence: 81%
“…Another study reported normal plasma and tissue OSI levels in rheumatic HVD, in spite of low tissue TAC levels (17). On the other hand, increased oxidative stress levels were demonstrated in the tissue and serum of patients with degenerative MR (26,36). In the present study, the levels of serum TAC, TOS, and OSI were found to be statistically similar in both the rheumatic and the congenital HVD groups.…”
Section: Discussionsupporting
confidence: 55%
“…To gain further insight into the intracellular biochemical consequences of VO, we have shown that cyclical stretch of adult rat cardiomyocytes increases XO activity and results in mitochondrial swelling, disorganization, and myofibrillar degeneration that is similar to the changes identified in the human LV with isolated mitral regurgitation (1,18). Treatment of stretched cardiomyocytes with allopurinol or the mitochondria-targeted antioxidant drug MitoQ prevents myofibrillar degeneration, mitochondrial damage, and the increase in XO activity (18).…”
mentioning
confidence: 84%
“…Recently, our laboratory has demonstrated increased cardiomyocyte oxidative stress in patients with VO of isolated chronic mitral regurgitation (1) and in rats with VO of aortocaval fistula (ACF) (18,39). Specifically, xanthine oxidase (XO) is elevated in cardiomyocytes along with myofibrillar degeneration and mitochondrial dysfunction and damage, despite a preserved LV ejection fraction (LVEF).…”
mentioning
confidence: 99%